Energy Harvesters: Flexible and Semi‐Transparent Thermoelectric Energy Harvesters from Low Cost Bulk Silicon (100) (Small 23/2013). Issue 23 (9th December 2013) - Sevilla, Galo Andres Torres; Inayat, Salman Bin; Rojas, Jhonathan Prieto; Hussain, Aftab Mustansir; Hussain, Muhammad Mustafa
<x xml:space="preserve">Abstract</x> Flexible and transparent high performance thermoelectric energy harvesters from low cost bulk silicon wafers are fabricated using existing silicon processes on silicon (100) and then peeled off from the original substrate leaving it for reuse. As reported on page 3916 by M. M. Hussain and co‐workers, the peeled off silicon has 3.6% thickness of bulk silicon reducing the thermal loss significantly and generating nearly 30% more output power than unpeeled harvesters. The demonstrated generic batch processing is a pragmatic way of peeling off a whole silicon circuit after conventional fabrication on bulk silicon wafers for extremely‐deformable, high‐performance integrated electronics. Design courtesy of Olga Kasimov. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>